Manajemen Kinerja Syariah: Inovasi Pengembangan Profesionalisme Kerja Berkelanjutan - Sulistiyah Sulistiyah; Nila Nafisatul Bashiroh; Heru Setyowiyono; Amalia Nuril Hidayati; Agus Eko Sujianto (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
Work professionalism has become an essential requirement in the modern era, characterized by technological advancements and increasing productivity demands. However, today’s workplace also faces various challenges, such as declining work ethics, low discipline, and an instant work culture. This study aims to analyze Sharia performance management as an innovation in developing sustainable work professionalism. The research method used is library research with a descriptive qualitative approach. The findings indicate that Sharia performance management emphasizes the values of trustworthiness, honesty, discipline, and responsibility in the workplace. These values are capable of shaping work professionalism that is oriented not only toward results but also toward work ethics and morality. Therefore, Sharia performance management is considered relevant in building high-quality and sustainable work professionalism in the modern era.